Bayar kemudian (BNPL) dan hutang: Zakat sebagai mekanisme kewangan bagi membantu komuniti asnaf di Malaysia. Suatu analisis konseptual melalui perspektif Maqasid Shariah dan legaliti Sharia - Sharif , Dziauddin; Mahyedin, Nur Shahidatul Akmar; Mustafar, Zaid; P. Rameli , Mohd Faizal (Journal of Islamic, Social, Economics and Development, 2026)
This conceptual study investigates the feasibility of zakat as a financial mechanism to support Buy Now Pay Later (BNPL) debt repayment among asnaf communities in Malaysia. Guided by Islamic literature, debt repayment is framed as a religious obligation requiring fairness, justice, and freedom from riba, while Maqasid Shariah emphasizes wealth preservation, accountability, and social welfare. Using a qualitative approach based on secondary data, findings show zakat supports al-gharimīn, mitigates vulnerability, and counters predatory lending. The study proposes a maqasid-consistent framework for zakat-assisted BNPL repayment, reinforcing Shariah principles and promoting socio-economic resilience.